Paleoenvironmental and neotectonic insights from the pliocene fossil record of Velika Pasica Cave, Slovenia: implications for karst system evolution - Mihevc, Andrej (Acta carsologica, 2025)
Velika Pasica Cave, situated on a karst plateau at an altitude of 665 meters above sea level, offers a unique record of paleontological, speleological, and tectonic processes. The cave, predominantly filled with allogenic sediments and speleothems, contains fossilized remains of the aquatic cave invertebrate Marifugia cavatica and terrestrial small mammals, characteristic of the early Pliocene (MN15–16). Paleontological dating estimates the cave sediments to be approximately 4 Ma old, while U/Th dating of the overlying flowstone indicates deposition at 410 ± 21 ka. These findings suggest that stagnant phreatic conditions prevailed prior to tectonic uplift and basin subsidence, which reshaped the karst landscape. This study highlights the dynamic interplay between neotectonics, karst system evolution, and biodiversity changes. By integrating speleobiology, geomorphology, and biostratigraphy, it provides valuable in-sights into the environmental history of the northern Dinarides and the impact of geological processes on karst ecosystems.
Keywords: cave sediments dating; datacija jamskih sedimentov; karst geomorphology; kraška geomorfologija; mali sesalci; Marifugia cavatica; paleontologija; paleontology; small mammals; tectonic; tektonika